Exploring An-Icons, Between Media Archaeology, Cultural History, Memory Studies and Contemporary Applications - Ampollini, Ilaria; Bandi, Fabrizia; Cavaletti, Federica; Conte, Pietro; Fontana, Margherita; Grossi, Giancarlo; Pinotti, Andrea; Pirandello, Sofia; Terrenghi, Ilaria (img journal, 2023)
The ERC Advanced Grant AN-ICON, coordinated by Andrea Pinotti and hosted by the Department of Philosophy Piero Martinetti of the University of Milan, is cross-disciplinary project that brings together aesthetics, media theory, archaeology and various disciplines to address the complexities of contemporary mediascape, particularly in the realm of Extended Reality (XR). Within XR, which encompasses Virtual Reality (VR), Augmented Reality (AR) and Mixed Reality (MR), ‘an-icons’ emerge as self-negating images that blur iconic boundaries and promote environmental presence. This paper provides an insight into AN-ICON’s diverse investigations dedicated to immersive technologies. It explores the cultural lineage of VR, AR and XR, their intersections with design and urban spaces, and the emerging prospects for digital memory studies. It also highlights the therapeutic, educational and prosocial potential of these media, informed by their historical and mediarchaeological backgrounds.